"Filmowy "Tatarak" Andrzeja Wajdy jako adaptacyjny tryptyk = Andrzej Wajda's "Sweet Rush" as a triptych film adaptation - Zwolińska, Barbara (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In this article I am interested in a particular type of film adaptation represented by "Sweet Rush" by Andrzej Wajda. The uniqueness of this adaptation is the use and contamination of four literary sources: Jarosław Iwaszkiewicz's stories, "Sudden Call" - a story by Sándor Márai and his drama "Adventure" as well as intimate writings of Krystyna Janda, who plays the lead character. One more piece may be added, "An Hour of Thought" by Juliusz Słowacki, cited in the short story "Sweet Rush" by Iwaszkiewicz. These sources, interestingly combined, share a common theme (of death and eroticism) and the climate of sensuality and melancholy, woven into the fabric of the film, played out in the Vistula outdoors, forming as it were the mental landscape of the characters' experiences.
Keywords: Iwaszkiewicz, Jarosław (1894-1980); adaptacja filmowa